Quality control of plastic sack products using the DMAIC method at PT. XYZ - Ismail, Ismail; Marwan, Marwan (International Journal of Mechanical Computational and Manufacturing Research, 2024)
PT. XYZ is a company engaged in the production of plastic sacks which are used for various industrial purposes. There are several types of defects in plastic sacks, namely, torn sacks, inappropriate sack brands, and slanted seams. This research aims to determine the level of product defects, factors causing product defects and provide suggestions for improvements to the production process at PT. XYZ. This research uses the six sigma method through the DMAIC stages (Define, Measure, Analyze, Improve and Control). Based on research results, the defect rate for plastic sack products was 2.72%, while the average level was 3.9 sigma. There are several factors that cause defects in plastic sack products, namely human factors, machines, work methods and materials. Proposed improvements to improve product quality at PT. XYZ there are several factors that must be improved, namely, humans are carrying out training and directing employees to follow SOPs, machines are making continuous maintenance schedules according to machine capacity so that they are always in good condition, work method factors the company must make additional SOPs so that work method problems are reduced. In the future, material is tightening the process of checking the inspection of threads that are not good properly.